Factors Influencing the Threats for Urban Energy Networks: The Inhabitants’ Point of View - Inna Čábelková; Wadim Strielkowski; Frank-Detlef Wende; Raisa Krayneva (Energies, 2020)
Our paper focuses on eliciting the factors that constitute threats and dangers for urban energy networks, information networks, and energy grids in the cities. Moreover, we attempt to determine how these threats are perceived by the inhabitants of those cities. Urban energy networks tend to play an increasing role in achieving energy efficiency and environmental sustainability in large urban centers. Even though they do not necessarily correspond to reality, public opinions can substantially influence the adoption of relevant technologies in populous urban locations. We use the public opinion representative survey data from the Czech Republic (a sample of 1023 respondents) in order to show how people perceive the dangers and threats for urban energy networks from such events as: (i) Extensive and long-term power outage; (ii) service disruption of the Internet, mobile networks or telephone landlines; (iii) cyber-attacks, and (iv) the technological dependence of the state on multinational technological companies. Our results demonstrate that people who live in small rural settlements and medium-sized cities tend to be more afraid of the threats and dangers from urban energy networks such as electricity and Internet outages, compared to people residing in some smaller towns. As far as there would always be a fear of the new technologies and their vulnerabilities, the local governments, mass media, and Internet resources alike should pay more attention to providing the relevant and updated information on the threats to urban energy networks for the general public.